1994
DOI: 10.1056/nejm199410063311402
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Postremission Chemotherapy in Adults with Acute Myeloid Leukemia

Abstract: These data support the concept of a dose-response effect for cytarabine in patients with AML who are 60 years of age or younger. The results with the high-dose schedule in this age group are comparable to those reported in similar patients who have undergone allogeneic bone marrow transplantation during a first remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
825
3
21

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,305 publications
(881 citation statements)
references
References 43 publications
24
825
3
21
Order By: Relevance
“…5 After receiving a timed-sequential induction therapy, complete remitters without allogeneic stem cell transplantation indication and related donor were randomized between the TSC ALFA-9000 consolidation 6 or 4 courses of high-dose cytarabine, according to the Cancer and Leukemia Group B (CALGB) schedule. 7 All patients registered on the study were randomized at registration to receive recombinant human GM-CSF (Leucomax, Schering Plough) given at a dose of 5 lg/kg/ day intravenously over 6 hours, from Day 1 through the last day of chemotherapy of each course (except salvage) of chemotherapy or no GM-CSF.…”
Section: Patients and Treatmentsmentioning
confidence: 99%
“…5 After receiving a timed-sequential induction therapy, complete remitters without allogeneic stem cell transplantation indication and related donor were randomized between the TSC ALFA-9000 consolidation 6 or 4 courses of high-dose cytarabine, according to the Cancer and Leukemia Group B (CALGB) schedule. 7 All patients registered on the study were randomized at registration to receive recombinant human GM-CSF (Leucomax, Schering Plough) given at a dose of 5 lg/kg/ day intravenously over 6 hours, from Day 1 through the last day of chemotherapy of each course (except salvage) of chemotherapy or no GM-CSF.…”
Section: Patients and Treatmentsmentioning
confidence: 99%
“…The pivotal randomized trial reported by Meyer and the Cancer and Acute Leukemia Group B (CALGB) colleagues compared consolidation therapy with high-dose cytarabine 3 g/m 2 IV over 2-3 hr every 12 hr on Days 1, 3, and 5 for 4 courses, to lower cytarabine dose schedules. High-dose cytarabine consolidations were followed by 4 additional courses of 2 1 5 chemotherapy [71]. The latter addition has been omitted from the subsequent comparative trials, an important consideration since later studies using this regimen as the standard of care reported five-year survival rates of 20-30% rather than 40% [72].…”
Section: Younger Patients With Amlmentioning
confidence: 99%
“…Studies indicate that post-remission intensification therapy with high dose cytarabine (HIDAC) decreases the risk of relapse for patients with AML in first complete remission [1,2]. However, disease recurrence still remains the most common cause of failure after HIDAC.…”
Section: Introductionmentioning
confidence: 99%